Reading Emotions in Faces With and Without Masks Is Relatively Independent of Extended Exposure and Individual Difference Variables - Carbon, Claus-Christian; Held, Marco Jürgen; Schütz, Astrid (Frontiers in Psychology, 2022)
The ability to read emotions in faces helps humans efficiently assess social situations. We tested how this ability is affected by aspects of familiarization with face masks and personality, with a focus on emotional intelligence (measured with an ability test, the MSCEIT, and a self-report scale, the SREIS). To address aspects of the current pandemic situation, we used photos of not only faces per se but also of faces that were partially covered with face masks. The sample (N=49), the size of which was determined by an a priori power test, was recruited in Germany and consisted of healthy individuals of different ages, M=24.8 [18-64] years). Participants assessed the emotional expressions displayed by six different faces determined by a 2 (sex) × 3 (age group: young, medium, old) design. Each person was presented with six different emotional displays (angry, disgusted, fearful, happy, neutral, and sad) with or without a face mask. Accuracy and confidence were lower with masks—in particular for the emotion disgust (very often misinterpreted as anger) but also for happiness, anger, and sadness. When comparing the present data collected in July 2021 with data from a different sample collected in May 2020, when people first started to familiarize themselves with face masks in Western countries during the first wave of the COVID-19 pandemic, we did not detect an improvement in performance. There were no effects of participants’ emotional intelligence, sex, or age regarding their accuracy in assessing emotional states in faces for unmasked or masked faces.